2010
DOI: 10.1016/j.healun.2010.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Supratherapeutic anticoagulation from low-molecular-weight heparin in lung transplant recipients

Abstract: Background-Venous thromboembolism (VTE) is common following lung transplantation. Enoxaparin is an approved therapy for VTE and anti-factor Xa (AXAL) can be used to monitor enoxaparin activity. Some studies have demonstrated elevated AXALs are associated with an increased risk of hemorrhage. Having identified a high incidence of supratherapeutic AXALs in lung transplant recipients, we aimed to elucidate the relationship between enoxaparin dose and AXAL in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…Our results are consistent with those of Singer et al. , who also found a high rate (67%) of supratherapeutic anti‐Xa levels in lung transplant recipients. In contrast to Singer's study, the majority of patients in our cohort received an empirically reduced enoxaparin dosage, including many receiving less than 0.8 mg/kg.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are consistent with those of Singer et al. , who also found a high rate (67%) of supratherapeutic anti‐Xa levels in lung transplant recipients. In contrast to Singer's study, the majority of patients in our cohort received an empirically reduced enoxaparin dosage, including many receiving less than 0.8 mg/kg.…”
Section: Discussionsupporting
confidence: 93%
“…Major bleeding episodes aligned with the expected rate cited in previous studies . Similar to other reports, we did not find a correlation between anti‐Xa levels and bleeding rates , although duration of enoxaparin was identified as risk factor for bleeding, resembling those seen in the non‐transplant population .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous data have demonstrated that patients with low anti-Xa activity increased 30-day mortality [19]. This may be due to the fact that the underdose of LMWH in our study doesn’t indicate low anti-Xa activity as LMWH has linear pharmacokinetics but high between-subject variability [20,21]. On the other hand, clinical outcomes are also influenced by patients’ characteristics and not only the dosage of LMWH.…”
Section: Discussionmentioning
confidence: 64%
“…Previously published case series in pregnancy and solid organ transplantation have demonstrated that standard weight-based dosing regimens have often resulted in an above goal AXAL. 5,6 In addition, studies in patients with renal failure suggest that enoxaparin requires dose reduction (either once-daily dosing at 1 mg/kg or twice-daily dosing at less than 1 mg/kg/dose) to achieve goal AXAL. [7][8][9] Finally, evidence in patients with morbid obesity suggests that even a conservative dosing strategy can lead to above goal AXAL.…”
Section: Introductionmentioning
confidence: 99%